The Amazing World of IDPs in Human Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
It is now clearly established that some proteins or protein regions are devoid of any stable secondary and/or tertiary structure under physiological conditions, but still possess fundamental biological functions. These intrinsically disordered proteins (IDPs) or regions (IDRs) have peculiar features due to their plasticity such as the capacity to bind their biological targets with high specificity and low affinity, and the possibility of interaction with numerous partners. A correlation between intrinsic disorder and various human diseases such as cancer, diabetes, amyloidoses and neurodegenerative diseases is now evident, highlighting the great importance of the topic. In this volume, we have collected recent high-quality research about IDPs and human diseases. We have selected nine papers which deal with a wide range of topics, from neurodegenerative disease to cancer, from IDR-mediated interactions to bioinformatics tools, all related to IDP peculiar features. Recent advances in the IDPs/IDRs issue are here presented, contributing to the progress of knowledge of the intrinsic disorder field in human disease.